Learning to Google: Understanding classed and gendered practices when young people use the Internet for research - Davies, H (SAGE Publications, 2017)
This article builds on existing research by examining two groups of young people, one from an elite fee-paying school and the other from a vocational college, as they engage with information on the Web about, for example, conspiracies, climate change and immigration. The data include the results of group and individual interviews, digital search terms and web (http) traffic, videos of discussions and downloads of arguments on social media. This study’s contribution is to synthesise digital methods and sociological concepts of technology, information and youth with Bourdieu’s social theory. By capturing offline and online events and decisions as they are manifested online (and vice versa), this study challenges distinctions between ‘the virtual’ and ‘the real’. It reveals how young people’s class of conditions, including their relative position in the United Kingdom’s educational hierarchy are played out in the way they use digital technology to produce intersecting classed and gendered practices.